Association between sleep bruxism and anxiety symptoms in adults: A systematic review. (12th March 2019) - Polmann, Helena; Domingos, Fabio Luiz; Melo, Gilberto; Stuginski‐Barbosa, Juliana; Guerra, Eliete Neves da Silva; Porporatti, André Luís; Dick, Bruce D.; Flores‐Mir, Carlos; De Luca Canto, Graziela
Summary: Background: The purpose of this systematic review was to evaluate the association between sleep bruxism (SB) and anxiety symptoms in adults. Methods: A systematic review was performed and studies assessing SB by means of questionnaires, clinical examination and/or polysomnography (PSG), and validated questionnaires to assess anxiety, were included. Search strategies were developed for seven main electronic databases. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross‐Sectional Studies, and confidence in cumulative evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation criteria. Results: Eight cross‐sectional studies were included, of which five were judged with low and three with moderate risk of bias. No association with SB was observed in three studies that investigated generic levels of anxiety, while other two papers that evaluated generic anxiety levels through the State‐Trait Anxiety Inventory (STAI) found a positive association with probable and definite SB in both STAI‐1 and STAI‐2 subscales. Only one study evaluated dental anxiety in particular and an association with probable SB was observed regarding very anxious or extremely anxious scores. Two studies assessed specific symptoms of anxiety using the panic‐agoraphobic spectra evaluation (PAS‐SR) questionnaire. Significantly higher PAS‐SR total scores were observed in both studies with regard to SB. No study with definitive assessment of SB was identified. Conclusion: Current literature is controversial regarding an association between SB and generic symptoms of anxiety in adults. It seems that some specific symptoms of the anxiety disorders spectrum might be associated with probable SB.